Understanding Maternal Intentions And Behaviors For Vaccine Preventable Diseases (Vpd) Control : A Structural Equation Modeling Analysis - Nur, Andi Fahira; Rahman, Nurdin; Fadjriah, Rasyika Nurul (Politeknik Kesehatan Kemenkes Mamuju, 2024)
The development of the health sector in Indonesia faces dual challenges of infectious and degenerative diseases. Immunization has proven to be an effective strategy in combating infectious diseases. However, achieving optimal immunization coverage remains a challenge. This study aimed to understand the factors influencing maternal intentions and behaviors in Vaccine Preventable Disease (VPD) control through immunization based on the Theory of Planned Behavior. Research methods is A Structural Equation Modeling (SEM) analysis was conducted to examine the relationships between constructs studied, namely Attitude, Subjective Norms, Perceived Control, Intention, and Behavior. Data were collected through a survey administered to a sample of mothers of toddlers. Results the SEM analysis revealed significant relationships between Attitude, Subjective Norms, Perceived Control, Intention, and Behavior. Attitude significantly influenced Intention, while Subjective Norms and Perceived Control indirectly influenced Intention. However, Subjective Norms and Perceived Control did not have a direct significant impact on Behavior. Conclusion this research is findings underscore the importance of Attitude, Subjective Norms, and Perceived Control in shaping maternal intentions and behaviors regarding VPD. Recommendations for improving maternal attitudes, subjective norms, perceived control, and intentions include educational strategies, social support, and enhancing accessibility to immunization services. By implementing these recommendations, it is hoped that the coverage and effectiveness of VPD immunization programs in Indonesia will be enhanced.